2020
DOI: 10.3892/ol.2020.11661
|View full text |Cite
|
Sign up to set email alerts
|

Identification of long non‑coding RNA SCARNA9L as a novel molecular target for colorectal cancer

Abstract: The aim of the present study was to analyze the microarray data of human colorectal cancer (CRC) tissues and identify novel therapeutic targets for CRC. Microarray analysis from the GSE73360 and GSE84984 datasets was performed to identify novel long non-coding RNAs (lncRNAs) that were differentially expressed in human CRC tissues. Additionally, small interfering RNAs were used to deplete the expression of the indicated lncRNAs in cells. Colony-formation, wound-closure, and transwell assays were performed on CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…In particular, some drugs targeting epigenetic modifications were developed astherapeutic molecularagainst CRC ( Patnaik and Anupriya, 2019 ). Among these epigenetic alterations, preliminary studies have demonstrated that non-coding RNAs such as long noncoding RNAs(lncRNAs) and miRNAs play crucial roles in prognosis and diagnosis of CRC ( De Robertis et al, 2018 ; Chai et al, 2020 ; Yu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, some drugs targeting epigenetic modifications were developed astherapeutic molecularagainst CRC ( Patnaik and Anupriya, 2019 ). Among these epigenetic alterations, preliminary studies have demonstrated that non-coding RNAs such as long noncoding RNAs(lncRNAs) and miRNAs play crucial roles in prognosis and diagnosis of CRC ( De Robertis et al, 2018 ; Chai et al, 2020 ; Yu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%